Performance measurement analysis of Sharia commercial banks in Indonesia with Maqashid Index and Sharia Conformity and Profitability (SCnP) - Andriansyah, Yuli; Masuwd, Mowafg; Asmar, Mohd. Dimasqi Abandi (Universitas Islam Indonesia, 2023)
IntroductionSharia-compliant banking plays a vital role in Indonesia's Islamic financial sector, balancing ethical principles and market competitiveness. However, assessing the performance of these banks requires tools that capture both financial viability and alignment with maqasid al-shariah, or the higher objectives of Sharia.ObjectivesThis study evaluates the performance of Indonesian Sharia-compliant banks using the Maqashid Index, which measures ethical contributions, and the Sharia Conformity and Profitability framework, which integrates financial outcomes with Sharia compliance. The research aims to identify key strengths and gaps in these banks' performance and compare the insights provided by these two frameworks.MethodA quantitative approach was adopted, analyzing data from five prominent Sharia-compliant banks in Indonesia over the 2010–2018 period. The Maqashid Index assessed contributions to education, justice, and public welfare, while the Sharia Conformity and Profitability framework evaluated financial performance and compliance with Islamic principles. Comparative analysis was employed to identify areas of alignment and divergence between the frameworks.ResultsThe findings revealed that while Bank Syariah Mandiri and Bank BNI Syariah excelled in both frameworks, others displayed significant gaps in education and public welfare contributions despite high Sharia compliance. Divergences between financial profitability and ethical objectives underscore the need for integrated performance metrics.ImplicationsThis study emphasizes the importance of balancing financial and ethical dimensions in Islamic banking. It provides actionable insights for policymakers and practitioners, suggesting a roadmap for enhancing both societal impact and financial sustainability.Originality/NoveltyThis study advances knowledge in Islamic banking by applying a dual-framework evaluation approach, highlighting the complementary roles of the Maqashid Index and Sharia Conformity and Profitability framework in assessing Sharia-compliant bank performance.